„Jak to jest być ośmiornicą”. Wywiad z Peterem Godfrey-Smithem - Godfrey-Smith, Peter; Kozhevnikova, Magdalena (Zoophilologica. Polish Journal of Animal Studies, 2025)
Philosopher Peter Godfrey-Smith discusses octopuses as key figures in his reflections on non-human consciousness and intelligence. He addresses the social behaviors observed in octopus colonies as well as their capacity for emotion and communication. He also speaks about the challenges of animal protection and the limits of ethical responsibility. Godfrey-Smith emphasizes the need to develop new ways of thinking about value and the lives of non-human beings.